Strong Responsivity Enhancement of Quantum Dot‐in‐a‐Well Infrared Photodetectors Using Plasmonic Structures. Issue 2 (28th November 2018) - Fowler, Clayton; Kim, Jun Oh; Lee, Sang Jun; Urbas, Augustine; Ku, Zahyun; Zhou, Jiangfeng
Abstract: Detector responsivity enhancement from integrating optimized plasmonic structure layers into quantum dot‐in‐a‐well photodetectors is investigated by a finite integration technique‐based simulation. It is found that by including a 0.1 µm thick gold hole‐array layer onto a backside illuminated photodetector, the peak detector responsivity is enhanced by nearly a factor of 8. A 0.2 µm thick gold disk‐array layer improves the peak responsivity by around 15 instead. The calculated enhancement factors show a good agreement with experimental data by Gu et al. [1] and Lee et al. [2] Simulation method and analytical analysis accomplished in this paper provide a generalized approach to design optimal plasmonic structures integrated to various infrared detecting device configurations. Abstract : Local field engineering based on Surface plasmons (SP) offers the possibility to step forward to the next generation of infrared detectors. A combined analytical and simulation method is developed to calculate the responsivity of quantum dot‐in‐a‐well IR photodetectors integrated with SP architectures. It is shown that an optimized SP configuration can enhance the detector performance by a factor of ≈40.